Utilizing Hand Puppet Media as a Strategy for Developing Moral Values in Early Childhood in the Digital Era - Fitriani Fitriani; Nur Fatimah; Debby Adelita Febrianti Purnamasari (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the utilization of hand puppet media in developing moral values in early childhood at RA Sunan Giri using a qualitative descriptive approach. The research subjects consisted of teachers and 15 children from Group B, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results of the study indicate that the use of hand puppet media can increase children's engagement in learning, help them understand moral values such as honesty, responsibility, discipline, and empathy, and improve their social interaction. In addition, this media serves as an effective alternative learning strategy to reduce children's dependence on gadget use while supporting character building from an early age. The contribution of this research lies in providing empirical evidence regarding the effectiveness of hand puppets as an innovative learning strategy for developing moral values in early childhood, while offering practical recommendations for teachers to integrate engaging, interactive learning media that aligns with children's developmental needs